Bez retushi . Bez retushi . Without Retouching . Без ретуши - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. The politician Gavriil Popov answers the questions of journalists and TV-audience. Featured in the program: Popov, Gavriil Kharitonovich (Politician) Contributors: Torchinskii, Sergei (Anchor); Krasnova, Tat'iana (Anchor) Политик Гавриил Попов отвечает на вопросы журналистов и телезрителей. В программе участвуют: Попов, Гавриил Харитонович (Политик) Создатели: Торчинский, Сергей (Ведущий/Ведущая); Краснова, Татьяна (Ведущий/Ведущая)